2017
DOI: 10.1590/1518-8345.1280.2841
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Incidents and Nursing Workload

Abstract: Objective:to identify the relationship between the workload of the nursing team and the occurrence of patient safety incidents linked to nursing care in a public hospital in Chile. Method:quantitative, analytical, cross-sectional research through review of medical records. The estimation of workload in Intensive Care Units (ICUs) was performed using the Therapeutic Interventions Scoring System (TISS-28) and for the other services, we used the nurse/patient and nursing assistant/patient ratios. Descriptive univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 19 publications
4
57
1
22
Order By: Relevance
“…[34] The results of this research are in line with results verified in other studies. [30,[34][35][36] In one of these studies, carried out with 195 patients, 43 (22%) developed HAI and, as in the present study, an excessive nursing workload was identified as a risk factor for HAI (OR: 11.41; p .019). [30] A metaanalysis, which included 38 studies, showed that in only 7 (18%) of the cases studied, it was not possible to observe a statistically significant relationship between variables that measure nursing team size and HAI rates.…”
Section: Discussionsupporting
confidence: 70%
“…[34] The results of this research are in line with results verified in other studies. [30,[34][35][36] In one of these studies, carried out with 195 patients, 43 (22%) developed HAI and, as in the present study, an excessive nursing workload was identified as a risk factor for HAI (OR: 11.41; p .019). [30] A metaanalysis, which included 38 studies, showed that in only 7 (18%) of the cases studied, it was not possible to observe a statistically significant relationship between variables that measure nursing team size and HAI rates.…”
Section: Discussionsupporting
confidence: 70%
“…A heavy workload has been found to be one of the most consistent stressors in the nursing profession (McVicar, ; Moore, Kuhrik, Kuhrik, & Katz, ; Tyler & Cushway, ) and has also been found to be related to anxiety, frustration (Spector, ), and burnout (Greenglass, Burke, & Fiksenbaum, ). In addition, work overload has been found to have a negative impact on healthcare workers' quality of care (Shirom, Nirel, & Vinokur, ) and has been associated with higher patient safety incidents (Carlesi, Padilha, Toffoletto, Henriquez‐Roldán, & Juan, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, this result was supported by the result of [30][31][32] ,whose results indicated that nurses' workload have been related to nurse assessed quality of care as it was an important determinant of quality of care. Also they reported that there was a direct relationship between nurses' workload and nurse-reported quality of care Moreover, this result was supported by [33][34][35][36] , whose results revealed that nursing work load affects care quality and mortality as it has strong relation with the quality of the care output that provided by the nurses so quality of nursing care can be improved by balanced distribution of workforce relative to workload in different shifts.…”
Section: Discussionmentioning
confidence: 89%